Variation of Chemical Elements and their Associations in Laterite Soil Profile - M Tufaila; La Ode Safiuddin; Rosliana Eso; Sitti Kasmiati; Hasbullah Syaf; La Ode Ahmad Nur Ramadhan; . Hasrorayan; . Ardin (JOURNAL OF TROPICAL SOILS, 2015)
The objective of this study was to evaluate the variations of twelve chemical elements (Ni, Fe, Co, Mg, Mn, Al, Si, Zn, Ti, P, Ca and Cr) in laterite soil profiles from Wantulasi area in South East Sulawesi Province of Indonesia. Eighty four (84) samples of three profiles (i.e. each profile consists of eight samples) had been used to study their variations in soil using  the X-Ray Fluorescence (XRF). Results analysis of the chemical elements content in three profile using XRF indicated that there were good correlationsbetween the chemical elements in the soil profile with the significant correlations were found in Ni and Fe, Ni and Si, Ti and P, Fe and Al, and Co and Mn, respectively. On the other hand,the results of study showed that the variations of the chemical elements could be related to the enrichment and translocation of the elements  in soil profile and also their possibilities to be related with a given chemical elements in soil profile. Therefore, we suggest that the observed patterns in chemical elements with a good correlation in laterite profile can be used as proxies to integrate the evaluation of the chemical and physical weathering process based on the elements characteristics in soil profiles.